O espetáculo semiótico do maracatu rural da zona da mata norte pernambucana - Moura, Adriano Carlos de (2016)
The central purpose of this work is situate rural maracatu among the cultural events in the state of Pernambuco, as a semiotic show. For this purpose, we use theory and methodology of French or greimasian semiotics. We assume that the rural maracatu is being constituted from various ethnic, social, religious and cultural influences. We also aim to point out what the main actors, themes and figures taking part in this magnificent popular festivity of the Zona da Mata of Pernambuco state; and we analyze the rural maracatu choreographic acquis from the roles each character plays in the dance. Taking into account the relevance of chosen maracatus and the visual quality of DVDs, we selected four presentations: Maracatu Estrela de Ouro de Aliança and Leão Misterioso , that occurred during the Annual Meeting of Rural Maracatus in Nazaré da Mata-PE, in 2009; and presentations of maracatus Coração Nazareno and Cambinda Brasileira, which took place during the Annual Meeting of Rural Maracatus, in 2011. From the analysis of generative course of meaning of the poetic compositions of the maracatu masters, we realized that, due to the inherent improvisation to performances in public square the subject of enunciation, which often plays a role of an enunciator-actor, is emerging in many narrative actants, themes and figures related to issues of interest to the communities in which they operate and that arise from the interaction with the audience. In presentations we reviewed, for example, topics were discussed related to football, politics, the environment, education, public safety, feminine statement, the Christian religion etc. In rural maracatu, we find characters such as Mateus, Catirina and burrinha, which can be seen in the cavalo-marinho and the bumba meu boi. In turn, king, queen, maid of palace, ambassadors, princes, princesses and even baianas come from maracatu nação. Virtually every rural maracatu master is or has been master of bumba meu boi or master-cirandeiro which proves, once again, the maracatu's relationship with other popular festivities. They were present in the maracatu loose thud, hieratic and totemic elements related to Catholicism, Candomblé and Catimbó. In addition, the orchestra and the terno that dictate the pulsating rhythm of maracatu usually perform frevo, coco, sieves or samba de matuto during the dance, which do not have a rigidity regarding the choreographic script. Finally, we argue that rural maracatu is a true amalgam of popular culture of Pernambuco.